Digital community management for crime prevention and public safety: strategies for safer and more inclusive online communities - Araghi, Sebastian (2025)
As social media platforms become central to community communication and engagement, they present both new opportunities and challenges for the prevention, disruption, and reduction of crime through digital public spaces. This article presents findings from a rapid evidence assessment (REA) conducted to inform the Queensland Police Service’s Digital Community Safety Champions initiative, focusing on four interrelated areas: de-escalation of online conflicts; dissemination of crime and safety information; best practices for managing crime-focused online communities; and the broader impact of social media on public safety. The REA synthesized evidence from peer-reviewed literature and grey sources published from 2013 up to February 2025, drawing on insights from policing, digital communication, and online community governance. The findings emphasize the importance of context-sensitive moderation strategies grounded in neutrality, timeliness, and discretion. Digital tools that promote deliberative dialogue, such as TruthMapping, can support structured engagement and reflection, while post-conflict review strengthens long-term moderation practices. Effective crime communication strategies should combine accuracy, accessibility, visual clarity, and multilingual content to enhance community responsiveness. Best practices for managing online crime communities include establishing clear group norms, safeguarding privacy, building trust through transparency, and avoiding vigilantism through responsible content governance. Finally, while social media offers new avenues for connection and public safety outreach, particularly for vulnerable groups, it also carries risks related to misinformation, radicalization, and surveillance. The article concludes with practical recommendations for moderators, platform designers, and policing stakeholders to help create safer, more ethical, and inclusive digital environments.